Studi Biofisik pada Lanskap Hutan Rawa Gambut di Taman Nasional Sebangau: Kasus di Resort Mangkok - Qirom, Muhammad Abdul; Halwany, Wawan; Rahmanadi, Dony; Tampubolon, Agustinus Panusunan (Jurnal Ilmu Pertanian Indonesia, 2019)
Fire and illegal logging are main causes of peat swamp forest (PSF) degradation. Degradation causes biotic and abiotic changes of PSF. This reasearch was designed to collect data on description of species composition, carbon stock, soil physical factors, and soil macrofauna as indicators of changes in land condition due to PSF degradation. This research was conducted on degraded PSF area caused by fire and illegal logging. Sample plots were located based on the distance from the river i.e.,